Carotid Atherosclerosis and Stroke in Atrial Fibrillation: The Atherosclerosis Risk in Communities (ARIC) Study - Bekwelem, Wobo (Stroke, 2016)
BACKGROUND AND PURPOSE: Whether consideration of carotid intima-media thickness (cIMT) and carotid plaque would improve risk prediction of ischemic stroke in persons with atrial fibrillation (AF) is unknown. The purpose of this study was to assess the improvement in risk prediction of stroke by adding cIMT and carotid plaque to the CHA(2)DS(2)-VASc score. METHODS: We included participants from the ARIC study (mean age, 63 years) who developed AF within 5 years after carotid measurement, were not on warfarin, and had no prior stroke at AF diagnosis. AF was ascertained from study ECGs and diagnosis codes, and stroke was physician-adjudicated. Multivariable Cox models were used to assess association between carotid indices and ischemic stroke. Improvement in 10-year risk prediction of stroke was assessed by the C-statistic, net reclassification improvement (NRI), and relative integrated discrimination improvement (IDI). RESULTS: There were 81 (11.2%) stroke events that occurred among 724 participants with AF during a mean follow-up of 8.5 years. Increased cIMT and presence of carotid plaque were significantly associated with increased stroke risk. The addition of cIMT + plaque to the CHA(2)DS(2)-VASc score marginally increased the C statistic (95% CI) from 0.685 (0.623–0.747) to 0.698 (0.638–0.759). The NRI and IDI for cIMT + plaque were 0.091 (95% CI, 0.012–0.170) and 0.101 (95% CI, 0.002–0.226), respectively. CONCLUSIONS: Increased cIMT and presence of carotid plaque are associated with increased risk of ischemic stroke in individuals with AF. Further, they may improve risk prediction of stroke, over and above the CHA(2)DS(2)-VASc score.